STRATEGIES AND PROSPECTS OF SUSTAINABLE DEVELOPMENT OF CITIES IN UKRAINE - ANFILOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the potential of implementing the SPARC system in Kyiv as a sustainable solution for urban mobility. SPARC combines real-time intelligent parking management with bidirectional electric vehicle (EV) charging, aiming to optimize the use of urban resources, reduce traffic congestion, and improve air quality. The system also promotes the adoption of electric transport, contributing to a greener and more energy-efficient city. Furthermore, the article emphasizes the importance of adapting the system to contemporary challenges such as climate change, rapid urbanization, and economic instability. The integration of SPARC into Kyiv’s infrastructure offers a unique opportunity to enhance the resilience of the city’s energy system while simultaneously creating a smart and eco-friendly urban environment. One of the key aspects discussed in the article is the necessity of effective communication with the public to ensure the successful implementation of SPARC. Public engagement, supported by educational programs and community involvement, plays a crucial role in raising awareness, forming ecological consciousness, and encouraging citizens to adopt new technologies and sustainable practices. The article also highlights the significance of collaboration between local authorities, businesses, and the scientific community, ensuring a comprehensive approach to solving urban challenges. The financial aspect of SPARC’s implementation is another critical consideration, as securing investments, grants, and public-private partnerships will be essential to the project’s success. By promoting innovation and fostering interdisciplinary cooperation, SPARC can serve as a model for other cities seeking to implement smart, sustainable mobility solutions. The article concludes that the integration of SPARC in Kyiv not only addresses current mobility and environmental issues but also contributes to the creation of a resilient, energy-efficient, and future-proof urban space, ultimately improving the quality of life for residents and paving the way for a more sustainable future.